Penggunaan Model Pembelajaran Think Talk Write (TTW) Untuk Meningkatkan Keterampilan Membaca Pemahaman Pada Peserta Didik Kelas IV Sekolah Dasar - Asfi Isyana Kusuma Astuti (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research is to improve reading comprehension skills in fictional texts through the use of the Think Talk Write (TTW) learning model at fourth grade students at SDN Jenengan 3 Boyolali in academic year 2018/2019. This research is a Classroom Action Research (CAR) which was done in two cycle. In each cycle consists of the planning, implementation, observation and reflection stages. The subjects of this research was researchers, fourth grade teachers and fourth grade students with 28 students. Data collection techniques in this research are observation, interviews, tests, and documentation. The technique used to check the validity is triangulation technique. The data analysis technique used in this research is a comparative descriptive technique and interactive analysis techniques. Data analysis includes: data reduction, explanation, data (data display) and conclusion. The results of this research show the average class also increased, at the pre-action stage 45.71 with classical completeness of 28.57% then in the first cycle it increased to 65.65 with classical completeness of 42.85% and in the second cycle it increased to 79.46 with classical completeness of 89.28%. Based of the result, the conclusion Think Talk Write (TTW) learning model can improve the reading comprehension skill of fourth grade student at SDN Jenengan 3 Boyolali in academic year 2018/2019.                Keywords: think talk write (TTW) model, skills, reading comprehension, elementary school